الاعتقاد بعالمٍ منصفٍ أو غير منصفٍ "مقالة بحثية" - كحيلة ريم (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
يسلطُ هذا البحث الضوء على الحاجة إلى "الاعتقاد" من منظور علم النفس، فقد بَرهنت الأبحاث العلمية المتعلقة بمواجهة التهديدات وخبرات الخسارة والتغلب عليها على وجود حاجتين للتفسير مستقلتين Davis, et. al., 1998, P561))، الأولى: تكون الرغبة في إدراك شيء ما في وضع عدائي مكروه على أنه وضع إيجابي؛ حيث يُصرَّح أو يُعبر هنا غالباً عن إعادة تقييمات وجودية (الآن أعرف ماذا يكون هاماً في حياتي)، أو عن خبرات اجتماعية إيجابية (لقد أدركت أنني أستطيع أن أعتمد على أسرتي)؛ إن مثل هذه التفسيرات الجديدة الإيجابية تكون أكثر احتمالية، كلما تميز الفرد بمرونة عقلية في التفكير، واتسم بتسامح مع الآخرين ((Dalbert,1996, P36. الثانية: تكون الرغبة في إيجاد معنى من الحوادث، وقد نُوقشت هذه الحاجة لإيجاد معنى أعمق في مجال بحث العالم المنصف. سَنعرض في هذا البحث أولاً فرضية العالم المنصف لـ ليرنير (Lerner) (1965-1980) وسنلخص أهم النتائج لـ 40 سنة من البحث في العالم المنصف، وسنخصص الجزء الثاني لتنظيم بحث العالم المنصف في نموذج منفصل شامل لدافع الإنصاف، بحيث يُميز بين ردود الفعل الحدسية والانعكاسية لموضوع الإنصاف. ونوضح في الختام العلاقة بين التدين والاعتقاد بالعالم المنصف. This research highlights the need to "Belief" from the perspective of psychology, scientific research related to confront threats and experiences of loss and overcome it proved the existence of two needs independent for interpretation (Davis, et. al., 1998, P561), first: the desire to realize something in a hostile disliked, that it a positive attitude; where expresses here often for existential re-evaluations (now I know what is important in my life), or for positive social experiences (I’ve realized that I can rely on my family); such new positive interpretations are more likely, whenever a person characterized by mental flexibility in thinking and tolerance with others (Dalbert, 1996, P36). Second: the desire to find the meaning of accidents, this has been discussed the need to find a deeper meaning research in the field of the just World. First, in this paper We’ll show hypothesis of the Just World by Lerner (1965-1980) and will summarize the most important results of 40 years of research in the just world, and will dedicate the second part of the research for the organization of research just world in a separate form a comprehensive justice motive, so that distinguish between intuitive reactions and the reflectivity of the subject justice. In conclusion, clarify the relationship between religiosity and belief in the just world.